Makara Candi Adan-Adan: Gaya Seni Masa Kaḍiri - Sukawati Susetyo (Berkala Arkeologi, 2020)
This paper discusses the makara found at Adan-Adan Temple, Kediri. So far, it is the largest makara in Indonesia and, in terms of iconography, has distinctive features. The data was collected through detailed observations both directly in the field or through photographs. This study employed a comparative analysis, i.e. comparing the collected data to the makaras from different periods (the Ancient Matarām, the Srīwijaya, and the Siŋhasāri). From these comparisons, it is known that the makara at Adan-Adan Temple has special characteristics, i.e. different depictions between the makara on the left and the right as can be seen from the figure of a mythical creature inside the makara’s mouth, from the sculpture on the front of the makara, and on the back of the makara. This particularity may be included as an art style of the Kaḍiri period (the transitional period of from Ancient Matarām to Siŋhasāri).